Five-Year Predictors of Insulin Initiation in People with Type 2 Diabetes under Real-Life Conditions - Sandro Gentile; Felice Strollo; Francesca Viazzi; Giuseppina Russo; Pamela Piscitelli; Antonio Ceriello; Carlo Giorda; Piero Guida; Paola Fioretto; Roberto Pontremoli; Salvatore De Cosmo; the AMD-Annals Study Group (Journal of Diabetes Research)
We performed a real-life analysis of clinical and laboratory parameters, in orally treated T2DM patients aiming at identifying predictors of insulin treatment initiation. Overall, 366955 patients (55.8% males, age 65 ± 11 years, diabetes duration 7 ± 8 years) were followed up between 2004 and 2011. Each patient was analyzed step-by-step until either eventually starting insulin treatment or getting to the end of the follow-up period. Patients switching to insulin showed a worse global risk profile, longer disease duration (10 ± 9 years vs. 6 ± 7 years, respectively; p<0.001), higher HbA1c (8.0 ± 1.6% vs. 7.2 ± 1.5%, respectively; p<0.001), higher triglycerides, a greater prevalence of arterial hypertension, antihypertensive, lipid-lowering and aspirin treatment, a higher rate of nonproliferative/proliferative retinopathy, and a nearly 4 times lower prevalence of the “diet alone.” They also showed a higher prevalence of subjects with eGFR < 60 ml/min/1.73 m2 (24.0% vs. 16.2%, respectively; p<0.001). Multivariate analysis identified diabetes duration, HbA1c, triglyceride and low HDL-C values, presence of retinopathy or renal dysfunction, and sulphonylurea utilization (the risk being approximately 3 times greater in the latter case) as independent predictors of insulin treatment initiation. LDL-C, lipid-lowering treatment, and overweight/obese seem to be protective. Results of tree analysis showed that patients on sulphonylurea, with high HbA1c, eGFR below 50 ml/min/1.73 m2, and at least 5-year disease duration, are at very high risk to start insulin treatment. We have to stick to this real-life picture, of course, until enough data are collected on patients treated with innovative medications which are expected to improve beta cell survival and further delay treatment-related insulin requirement.